PENGARUH LITERASI KEUANGAN, GAYA HIDUP DAN PENDAPATAN TERHADAP PERILAKU KEUANGAN GENERASI Z DI KABUPATEN NABIRE - Nuril Fikri Mukti Pramundari; Teti Anggita Safitri (MANAJEMEN DEWANTARA, 2025)
This study aims to determine the influence of financial literacy, lifestyle, and income on the financial behavior of Generation Z in Nabire Regency. This study used quantitative research with multiple regression analysis. The sample used was students, employees, young workers, entrepreneurs, government or private sector employees belonging to the Generation Z category who reside in Nabire Regency, have a source of income, and are active in personal financial activities.The results obtained after data analysis indicate that financial literacy has a significant influence on the financial behavior of Generation Z in Nabire Regency. Lifestyle and income do not significantly influence the financial behavior of Generation Z in Nabire Regency. Simultaneously, financial literacy, lifestyle, and income influence the financial behavior of Generation Z in Nabire Regency.